Contribution of Thermohaline Staircases to Deep Water Mass Modifications in the Western Mediterranean Sea From Microstructure Observations - Ferron, Bruno; Bouruet-Aubertot, Pascale; Schroeder, Katrin; Bryden, Harry L.; Cuypers, Yannis; Borghini, Mireno (Frontiers in Marine Science, 2021)
Recent observations from profiles of temperature and salinity in the Algerian Sea showed that salt finger mixing can significantly warm and salinify the deep waters within a period of 2 years, thereby contributing to the erosion of deep water properties formed during winter convection episodes. In this study, heat, salt, and buoyancy fluxes associated with thermohaline staircases are estimated using microstructure observations from four locations of the Western Mediterranean Sea: The Tyrrhenian Sea, the Algerian Sea, the Sardino-Balearic Sea, and the Ligurian Sea. Those fluxes are compared to the rare estimates found in the Mediterranean Sea. Microstructure data show that the temperature variance dissipation rate is one to three orders of magnitude larger in the strong steps that separate weakly stratified layers than in the layers, while the turbulent kinetic energy dissipation rate remains usually weak both in steps and layers. In the steps, the turbulent eddy diffusivity of salt is on average twice as large as that of temperature. The buoyancy flux ratio decreases with the density ratio. It is found that staircases induce a downward heat transfer rate of 46 to 103 × 109 W over the whole western basin, and a downward salt transfer rate of 4.5 to 10.3 × 103 kg s–1 between 1000 and 2000 m. This heat convergence is 2–5 times as large as the western Mediterranean geothermal heat flux in this depth range. Over the whole western basin, heat and salt convergences from salt-fingering staircases are 50% to 100% of those generated by mechanical mixing. Finally, it is found that heat and salt convergences from geothermal heating, salt-fingering and mechanical mixing can balance a deep water upwelling of 0.4 × 106 m3 s–1.